Lakaki As a Form of Curriculum Adaptation for Learning Electrical Circuits Material for the Sixth Grade Students of SD Negeri Demakijo 2 Sleman Regency Academic Year 2023/2024 - Sutarti S; Ana Fitrotun Nisa; Berliana Henu Cahyani (Indonesian Journal of Primary Education, 2023)
Science learning in elementary schools is influenced by, among other things, interactive learning experiences. Interactive learning involves the activities of all students with various characteristics. An interactive learning experience will support the successful learning outcomes of all students. In reality, teachers face a diversity of student characteristics, one of which is related to different cognitive abilities. The aim of this research is to determine the success of the learning outcomes of all students through the Lakaki "Lamp Our Cafe" Project. This research is a classroom action research (CAR) model by Kemmis Mc. Taggart is carried out in two planned cycles. The stages include planning, action, observation and reflection. The subjects in this research were the sixth grade students at one of the state elementary schools in Sleman. The research was carried out by providing action in the form of a project to make decorative lamps using residual items found in the surrounding environment. The implementation of the Lakaki project carried out observations, interviews and documentation of student learning outcomes. The Lakaki project steps include: orienting students to problems, organizing students to learn, guiding individual/group investigations, developing and presenting results, analyzing and evaluating the problem solving process carried out in blended learning. The results of the research showed that there was an increase in student learning outcomes from cycle 1 with method completeness of 57.15% and a class average of 72.00. Cycle 2 learning completion reached 100%, with an average final score of 94.18. This proves that the Lakaki project is an alternative learning method to meet the diversity of students, especially the diversity of different cognitive abilities.